High-transmittance double-silver coated laminated glass for automobile front windshield and preparation method of high-transmittance double-silver coated laminated glass

By using high-transmissive double-silver coated laminated glass on the front-mounted glass, and using the combination of multi-layer film and PVB glue, the problem of reduced transmittance of the coated glass is solved, high transmittance and excellent sunshade performance are achieved, and driving experience and safety are improved.

CN120003115APending Publication Date: 2025-05-16QINGDAO FLOAT GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510099756.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-16

AI Technical Summary

Technical Problem

The transmittance of existing coated glasses has decreased in the automotive field, making it difficult to increase the sunshade coefficient to reduce the entry of solar radiation without affecting the visible light transmittance and safety intensity.

Method used

Highly transparent double silver coated laminated glass is used to coat multiple film layers on the outer glass substrate, including AZO, ZTO, Si3N4, NiCr, Ag and ZrO2, and laminate transparent PVB glue layers on it to form an optimized film structure to improve transmittance and sunshade performance.

Benefits of technology

The light transmittance of double silver coated glass is improved, the sunshade performance and the ability to block sunlight are enhanced, the air conditioner usage rate in the car is reduced, the temperature in the car is stabilized, the driving experience is improved, and driving safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120003115A_ABST
    Figure CN120003115A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coated glass, and particularly discloses high-transmittance double-silver coated laminated glass for a front windshield of an automobile and a preparation method of the high-transmittance double-silver coated laminated glass. The problem that the transmissivity of the coated glass applied to the field of automobiles is reduced is effectively solved. Comprising an outer glass substrate, a transparent PVB glue layer and an inner glass substrate, and a first surface of the outer glass substrate is sequentially provided with a first film layer, a second film layer, a third film layer, a fourth film layer, a fifth film layer, a sixth film layer, a seventh film layer, an eighth film layer, a ninth film layer, a tenth film layer, an eleventh film layer, a twelfth film layer and a thirteenth film layer outwards; the third film layer, the sixth film layer, the eighth film layer and the eleventh film layer are made of AZO, the second film layer and the seventh film layer are made of ZTO, the first film layer and the twelfth film layer are made of Si3N4, the fifth film layer and the tenth film layer are made of NiCr, the fourth film layer and the ninth film layer are made of Ag, and the thirteenth film layer is made of ZrO2. And the PVB adhesive layer is arranged between the thirteenth film layer and the inner glass substrate. The fabric has high transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coated glass, and in particular relates to a high-transmittance double-silver coated laminated glass for a car windshield and a preparation method thereof. Background Art

[0002] Ordinary glass is widely used in the automotive field because of its high transmittance to achieve the function of broadening the field of vision. At present, due to the demand for cruising range of new energy vehicles and the carbon emission policy of fuel vehicles, the requirements for comfort and energy saving in the car cabin are getting higher and higher, and the heat loss through the glass is the main part of the energy consumption of automobile air conditioning (accounting for more than 50%). Relevant research data show that the heat transfer of solar direct transmittance glass is mainly solar thermal radiation (accounting for 80%), which means that the loss of heat energy must be reduced by changing the performance of the glass, and the most effective way is to suppress the solar radiation of sunlight through the glass, and increase the shading coefficient of the front windshield without affecting the visible light transmittance and safety strength required by laws and regulations. Therefore, double silver or triple silver low-emissivity coated glass began to be used in the automotive field. Summary of the invention

[0003] One object of the present invention is to provide a high-transmittance double-silver coated laminated glass for automobile windshields, which effectively solves the problem of decreased transmittance of coated glass used in the automotive field.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-transmittance double-silver-coated laminated glass for automobile windshields, comprising an outer glass substrate, a transparent PVB adhesive layer and an inner glass substrate, wherein the outer glass substrate and the inner glass substrate both comprise a first surface and a second surface opposite to each other, a coating film layer is provided on the first surface of the outer glass substrate, and the coating film layer comprises a first film layer, a second film layer, a third film layer, a fourth film layer, a fifth film layer, a sixth film layer, a seventh film layer, an eighth film layer, a ninth film layer, a tenth film layer, an eleventh film layer, a twelfth film layer and a thirteenth film layer sequentially from the first surface of the outer glass substrate to the outside.

[0005] The materials of the third film layer, the sixth film layer, the eighth film layer and the eleventh film layer are all AZO, the materials of the second film layer and the seventh film layer are all ZTO, the materials of the first film layer and the twelfth film layer are all Si3N4, the materials of the fifth film layer and the tenth film layer are all NiCr, the materials of the fourth film layer and the ninth film layer are all Ag, and the material of the thirteenth film layer is ZrO2.

[0006] The PVB adhesive layer is arranged between the thirteenth film layer and the second surface of the inner glass substrate.

[0007] Further, the thickness of the first film layer is 6 to 8 nm, the thickness of the second film layer is 7 to 10 nm, the thickness of the third film layer is 18 to 20 nm, the thickness of the fourth film layer is 7 to 10 nm, the thickness of the fifth film layer is 0.5 to 2 nm, the thickness of the sixth film layer is 7 to 10 nm, the thickness of the seventh film layer is 65 to 67 nm, the thickness of the eighth film layer is 13 to 15 nm, the thickness of the ninth film layer is 10 to 12 nm, the thickness of the tenth film layer is 0.5 to 2 nm, the thickness of the eleventh film layer is 7 to 10 nm, the thickness of the twelfth film layer is 23 to 25 nm, and the thickness of the thirteenth film layer is 3 to 5 nm.

[0008] Furthermore, the thickness of the PVB adhesive layer is 0.76 mm.

[0009] Furthermore, the outer glass substrate and the inner glass substrate are both plain white glass plates with a thickness of 2.1 mm.

[0010] Furthermore, the third film layer, the sixth film layer, the eighth film layer and the eleventh film layer AZO film layer are formed by magnetron sputtering using aluminum-doped zinc oxide as a target material, the first film layer and the twelfth film layer Si3N4 film layer are formed by magnetron sputtering using rotated silicon as a target material, the thirteenth film layer ZrO2 film layer is formed by magnetron sputtering using zirconium oxide as a target material, and the second film layer and the seventh film layer ZTO film layer are formed by magnetron sputtering using zinc tin oxide as a target material.

[0011] Another object of the present invention is to provide a method for preparing the high-transmittance double-silver coated laminated glass for automobile windshields as described in the above embodiments, comprising the following steps: S1, coating target material: silicon aluminum alloy, zinc aluminum alloy, nickel chromium alloy, silver, zinc tin oxide and zirconium oxide are respectively installed on the target position of the vacuum magnetron sputtering chamber of the glass coating machine, the chamber is evacuated, the process gas is passed, and the target is burned for standby use.

[0012] S2. Pretreatment of glass: placing the inner glass substrate and the outer glass substrate to be coated under vacuum, dehumidifying and degassing the inner glass substrate and the outer glass substrate to be coated, so as to reduce the moisture and gas deposited on the surfaces of the outer glass substrate and the inner glass substrate.

[0013] S3, coating treatment: sending the outer glass substrate after the dehumidification and degassing treatment in step S2 into the vacuum magnetron sputtering chamber of the glass coating machine, and coating the first surface of the outer glass substrate with a first film layer, a second film layer, a third film layer, a fourth film layer, a fifth film layer, a sixth film layer, a seventh film layer, an eighth film layer, a ninth film layer, a tenth film layer, an eleventh film layer, a twelfth film layer and a thirteenth film layer in sequence from bottom to top to obtain coated glass.

[0014] S4, sintering treatment: sinter the coated glass at 650°C for 400 seconds.

[0015] S5. Lamination treatment: 0.76 mm transparent PVB is used as a glue layer to perform lamination treatment between the thirteenth film layer on the outer glass substrate and the second surface of the inner glass substrate to obtain a high-transmittance double-silver-coated laminated glass.

[0016] Furthermore, before the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥ 61%, and the visible light reflectivity of the glass surface of the coated glass is ≤ 8%.

[0017] After the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤9%.

[0018] Furthermore, after the lamination treatment in step S5, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤11%.

[0019] Furthermore, after the lamination treatment in step S5, the reflected light A value of the coated surface of the coated glass at an incident angle of 8° is -8.96±2.5, and the reflected light B value is -11.79±2.5.

[0020] After the lamination treatment in step S5, the coating surface of the coated glass reflects light at an incident angle of 60° with an A value of -1.89±2.5 and a B value of -5.06±2.5.

[0021] After the lamination treatment in step S5, the glass surface of the coated glass reflects light at an incident angle of 8° with an A value of -6.77±2.5 and a B value of -13.46±2.5.

[0022] After the lamination treatment in step S5, the glass surface of the coated glass reflects light at an incident angle of 60° with an A value of -8.96±2.5 and a B value of -11.79±2.5.

[0023] Furthermore, the light transmittance of the high-transmittance double-silver coated laminated glass exceeds 70%, and the glass haze is 0.36%.

[0024] Compared with the prior art, the beneficial technical effects of the present invention are:

[0025] The present invention improves the light transmittance of the double silver coated glass. When the present invention is applied to the front windshield of an automobile, it does not obstruct the driver's sight because of its high transmittance; it has an SC value and a TTS value that are superior to those of ordinary laminated glass, so that the laminated glass can reduce the entry of infrared and ultraviolet rays as much as possible without affecting the sight, greatly blocks the entry of sunlight, reduces the use rate of air conditioning in the car, stabilizes the temperature in the car, greatly improves the driving experience, can protect the driver from sunburn, and can achieve the purpose of energy saving and emission reduction, thereby improving driving safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic structural diagram of the high-transmittance double-silver-coated laminated glass of Example 1.

[0027] Explanation of the accompanying drawings: outer glass substrate-1; PVB adhesive layer-2; inner glass substrate-3; first film layer-4; second film layer-5; third film layer-6; fourth film layer-7; fifth film layer-8; sixth film layer-9; seventh film layer-10; eighth film layer-11; ninth film layer-12; tenth film layer-13; eleventh film layer-14; twelfth film layer-15; thirteenth film layer-16. DETAILED DESCRIPTION

[0028] Embodiment 1: A high-transmittance double-silver coated laminated glass for automobile windshields, comprising an outer glass substrate 1, a transparent PVB adhesive layer 2 and an inner glass substrate 3. The outer glass substrate 1 and the inner glass substrate 3 both comprise a first surface and a second surface opposite to each other. A coated film layer is provided on the first surface of the outer glass substrate 1, and the coated film layer comprises a first film layer 4, a second film layer 5, a third film layer 6, a fourth film layer 7, a fifth film layer 8, a sixth film layer 9, a seventh film layer 10, an eighth film layer 11, a ninth film layer 12, a tenth film layer 13, an eleventh film layer 14, a twelfth film layer 15 and a thirteenth film layer 16 in order from the first surface of the outer glass substrate 1 to the outside. The PVB adhesive layer 2 is provided between the thirteenth film layer 16 and the second surface of the inner glass substrate 3.

[0029] The thickness of the first film layer 4 is 6-8 nm, the thickness of the second film layer 5 is 7-10 nm, the thickness of the third film layer 6 is 18-20 nm, the thickness of the fourth film layer 7 is 7-10 nm, the thickness of the fifth film layer 8 is 0.5-2 nm, the thickness of the sixth film layer 9 is 7-10 nm, the thickness of the seventh film layer 10 is 65-67 nm, the thickness of the eighth film layer 11 is 13-15 nm, the thickness of the ninth film layer 12 is 10-12 nm, the thickness of the tenth film layer 13 is 0.5-2 nm, the thickness of the eleventh film layer 14 is 7-10 nm, the thickness of the twelfth film layer 15 is 23-25 ​​nm, and the thickness of the thirteenth film layer 16 is 3-5 nm. The thickness of the PVB adhesive layer 2 is 0.76 mm.

[0030] The materials of the third film layer 6, the sixth film layer 9, the eighth film layer 11 and the eleventh film layer 14 are all AZO (zinc aluminum oxide), the materials of the second film layer 5 and the seventh film layer 10 are all ZTO, the materials of the first film layer 4 and the twelfth film layer 15 are all Si3N4, the materials of the fifth film layer 8 and the tenth film layer 13 are all NiCr, the materials of the fourth film layer 7 and the ninth film layer 12 are all Ag, and the material of the thirteenth film layer 16 is ZrO2.

[0031] The third film layer 6, the sixth film layer 9, the eighth film layer 11 and the eleventh film layer 14 are all AZO film layers, which are formed by magnetron sputtering using aluminum-doped zinc oxide as a target material; the first film layer 4 and the twelfth film layer 15 are both Si3N4 film layers, which are formed by magnetron sputtering using rotated silicon as a target material; the thirteenth film layer 16 is a ZrO2 film layer, which is formed by magnetron sputtering using zirconium oxide as a target material; the second film layer 5 and the seventh film layer 10 are both ZTO film layers, which are formed by magnetron sputtering using zinc tin oxide as a target material.

[0032] The first film layer 4 and the twelfth film layer 15 are Si3N4 film layers (silicon nitride layers), which are structural ceramic materials with high hardness, lubricity, wear resistance, oxidation resistance at high temperatures, and resistance to thermal shock; the fifth film layer 8 and the tenth film layer 13 are nickel-chromium alloy layers with high strength and corrosion resistance; the second film layer 5 and the seventh film layer 10 are ZTO layers with high light transmittance in the visible light range; the third film layer 6, the sixth film layer 9, the eighth film layer 11 and the eleventh film layer 14 are AZO layers with high conductivity and low resistivity; the thirteenth film layer 16 is a zirconium oxide layer, which is chemically inactive and has the properties of high melting point, high resistivity, high refractive index and low thermal expansion coefficient; the fourth film layer 7 and the ninth film layer 12 are silver particle layers with minimal polarization effect. Silver particles are important optical materials for applications in the visible light and near-infrared light regions.

[0033] In this embodiment, a nickel-chromium alloy layer and an AZO layer are symmetrically arranged on both sides of the silver particle layer as an isolation stabilization layer, and a protective layer (sacrificial layer) of the silver particle layer is partially oxidized. During the partial oxidation process, the visible light transmittance of the film layer will be improved, and the excellent optical properties of the silver particles make the coated glass more transparent.

[0034] In this embodiment, the first film layer 4 (bottom layer) and the twelfth film layer 15 (second top layer) are set as silicon nitride layers as insulating layers, and the thirteenth film layer 16 (top layer) is set as a zirconium oxide layer as a protective layer. The hardness, wear resistance and oxidation resistance at high temperatures of both layers are used to protect the coated film layer of the outer glass substrate 1, thereby improving the processing performance of the coated glass.

[0035] In this embodiment, the outer glass substrate 1 and the inner glass substrate 3 are both plain white glass substrates with a thickness of 2.1 mm, purchased from Taiwan Glass Qingdao Co., Ltd.

[0036] This embodiment greatly improves the transmittance and processing performance of high-transmittance double-silver coated laminated glass through the reasonable arrangement of the film layer structure and the design of the film layer thickness.

[0037] Example 2: The method for preparing high-transmittance double-silver-coated laminated glass for automobile windshields described in Example 1 comprises the following steps: S1, sintering target materials: sintering silicon-aluminum alloy, zinc-aluminum alloy, nickel-chromium alloy, silver, zinc-tin oxide and zirconium oxide respectively on the target position of the vacuum magnetron sputtering chamber of the glass coating machine and setting them aside.

[0038] S2. Pretreatment of glass: placing the inner glass substrate 3 and the outer glass substrate 1 to be coated in a vacuum state, and performing dehumidification and degassing treatment on the inner glass substrate 3 and the outer glass substrate 1 to be coated to reduce the moisture and gas deposited on the surfaces of the outer glass substrate 1 and the inner glass substrate 3.

[0039] S3, coating treatment: send the outer glass substrate 1 after the dehumidification and degassing treatment in step S2 into the vacuum magnetron sputtering chamber of the glass coating machine, and coat the first surface of the outer glass substrate 1 with a first film layer 4, a second film layer 5, a third film layer 6, a fourth film layer 7, a fifth film layer 8, a sixth film layer 9, a seventh film layer 10, an eighth film layer 11, a ninth film layer 12, a tenth film layer 13, an eleventh film layer 14, a twelfth film layer 15 and a thirteenth film layer 16 in sequence from bottom to top to obtain coated glass.

[0040] S4, sintering treatment: sinter the coated glass at 650°C for 400 seconds.

[0041] S5. Lamination treatment: 0.76 mm transparent PVB is used as a glue layer to perform lamination treatment between the thirteenth film layer 16 on the outer glass substrate 1 and the second surface of the inner glass substrate 3 to obtain a high-transmittance double-silver-coated laminated glass.

[0042] PVB is the abbreviation of polyvinyl butyral, which is the product of the condensation of polyvinyl alcohol and butyraldehyde under acid catalysis. Because the PVB molecule contains relatively long side chains, it has good flexibility, low glass transition temperature, high tensile strength and impact strength. PVB has excellent transparency, good solubility, good light resistance, water resistance, heat resistance, cold resistance and film-forming properties. The functional groups it contains can undergo various reactions such as saponification of acetyl, esterification and sulfonation of hydroxyl groups, and have high adhesion to materials such as glass and metal (especially aluminum). Therefore, it has been widely used in the manufacture of laminated safety glass, adhesives, ceramic flower paper, aluminum foil, electrical materials, fiberglass products, fabric treatment agents and other fields, and has become an indispensable synthetic resin material.

[0043] Before the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥61%, and the visible light reflectivity of the glass surface of the coated glass is ≤8%;

[0044] After the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤9%.

[0045] After the lamination treatment in step S5, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤11%.

[0046] After the lamination treatment in step S5, the glass surface of the coated glass reflects light at an incident angle of 8° with an A value of -6.77±2.5 and a B value of -13.46±2.5; the glass surface of the coated glass reflects light at an incident angle of 60° with an A value of -8.96±2.5 and a B value of -11.79±2.5.

[0047] After the lamination treatment in step S5, the coated surface of the coated glass reflects light at an incident angle of 8° with an A value of -8.96±2.5 and a B value of -11.79±2.5; the coated surface of the coated glass reflects light at an incident angle of 60° with an A value of -1.89±2.5 and a B value of -5.06±2.5.

[0048] The light transmittance of the high-transmittance double-silver coated laminated glass prepared in this embodiment exceeds 70%, and the glass haze is 0.36%. It can be used in automobile windshields and meets the standards for automobile glass. Haze is the percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity. The greater the haze, the lower the gloss and transparency of the film, especially the imaging degree. Therefore, haze is an important criterion for evaluating whether glass can be used in automobiles.

[0049] The shading coefficient (SC value) of the high-transmittance double silver-coated laminated glass provided in this embodiment is 44.1%, and the total solar transmittance (TTS value) is 38.1%. The laminated glass made of two 2.1mm plain white glass substrates and a 0.76mm transparent PVB adhesive layer is a comparative example, and the SC value of the comparative example is 95%, and the TTS value is 82.5%. Compared with the comparative example, the shading coefficient of this embodiment is smaller, indicating that the high-transmittance double silver-coated laminated glass provided in this embodiment has better performance in blocking light and heat radiation; the total solar transmittance of this embodiment is moderate, which is conducive to achieving a balance between lighting and heat insulation.

[0050] The high-transmittance double-silver coated laminated glass of the present invention can be applied to many fields, especially in the field of automobile manufacturing. The present invention improves the light transmittance of the double-silver coated glass. When the present invention is applied to the front windshield of an automobile, it does not obstruct the driver's sight because of its high transmittance performance; it has an SC value and a TTS value that are better than those of ordinary laminated glass, so that the laminated glass can reduce the entry of infrared and ultraviolet rays as much as possible without affecting the sight, greatly block the entry of sunlight, reduce the use rate of air conditioning in the car, stabilize the temperature in the car, greatly improve the driving experience, protect the driver from sunburn, and achieve the purpose of energy saving and emission reduction, thereby improving driving safety.

[0051] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A high-transmittance double-silver coated laminated glass for automobile windshield, characterized in that: It comprises an outer glass substrate, a transparent PVB adhesive layer and an inner glass substrate, wherein the outer glass substrate and the inner glass substrate each comprise a first surface and a second surface opposite to each other, a coating film layer is provided on the first surface of the outer glass substrate, and the coating film layer comprises a first film layer, a second film layer, a third film layer, a fourth film layer, a fifth film layer, a sixth film layer, a seventh film layer, an eighth film layer, a ninth film layer, a tenth film layer, an eleventh film layer, a twelfth film layer and a thirteenth film layer sequentially from the first surface of the outer glass substrate to the outside; The materials of the third film layer, the sixth film layer, the eighth film layer and the eleventh film layer are all AZO, the materials of the second film layer and the seventh film layer are all ZTO, the materials of the first film layer and the twelfth film layer are all Si3N4, the materials of the fifth film layer and the tenth film layer are all NiCr, the materials of the fourth film layer and the ninth film layer are all Ag, and the material of the thirteenth film layer is ZrO2; The PVB adhesive layer is arranged between the thirteenth film layer and the second surface of the inner glass substrate.

2. The high-transmittance double-silver coated laminated glass for automobile windshield according to claim 1, characterized in that: The thickness of the first film layer is 6 to 8 nm, the thickness of the second film layer is 7 to 10 nm, the thickness of the third film layer is 18 to 20 nm, the thickness of the fourth film layer is 7 to 10 nm, the thickness of the fifth film layer is 0.5 to 2 nm, the thickness of the sixth film layer is 7 to 10 nm, the thickness of the seventh film layer is 65 to 67 nm, the thickness of the eighth film layer is 13 to 15 nm, the thickness of the ninth film layer is 10 to 12 nm, the thickness of the tenth film layer is 0.5 to 2 nm, the thickness of the eleventh film layer is 7 to 10 nm, the thickness of the twelfth film layer is 23 to 25 nm, and the thickness of the thirteenth film layer is 3 to 5 nm.

3. The high-transmittance double-silver coated laminated glass for automobile windshield according to claim 2, characterized in that: The thickness of the PVB adhesive layer is 0.76 mm.

4. The high-transmittance double-silver coated laminated glass for automobile windshield according to claim 3, characterized in that: The outer glass substrate and the inner glass substrate are both plain white glass plates with a thickness of 2.1 mm.

5. The high-transmittance double-silver coated laminated glass for automobile windshield according to claim 4, characterized in that: The third film layer, the sixth film layer, the eighth film layer and the eleventh film layer AZO film layer are formed by magnetron sputtering using aluminum-doped zinc oxide as a target material, the first film layer and the twelfth film layer Si3N4 film layer are formed by magnetron sputtering using rotated silicon as a target material, the thirteenth film layer ZrO2 film layer is formed by magnetron sputtering using zirconium oxide as a target material, and the second film layer and the seventh film layer ZTO film layer are formed by magnetron sputtering using zinc tin oxide as a target material.

6. The method for preparing the high-transmittance double-silver coated laminated glass for automobile windshield according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Coating target: install silicon aluminum alloy, zinc aluminum alloy, nickel chromium alloy, silver, zinc tin oxide and zirconium oxide on the target position of the vacuum magnetron sputtering chamber of the glass coating machine respectively, evacuate the chamber, pass the process gas, and burn the target for standby; S2. Pretreatment of glass: placing the inner glass substrate and the outer glass substrate to be coated in a vacuum state, and performing dehumidification and degassing treatment on the inner glass substrate and the outer glass substrate to be coated to reduce the moisture and gas deposited on the surface of the outer glass substrate and the inner glass substrate; S3, coating treatment: sending the outer glass substrate after the dehumidification and degassing treatment in step S2 into the vacuum magnetron sputtering chamber of the glass coating machine, coating the first surface of the outer glass substrate with a first film layer, a second film layer, a third film layer, a fourth film layer, a fifth film layer, a sixth film layer, a seventh film layer, an eighth film layer, a ninth film layer, a tenth film layer, an eleventh film layer, a twelfth film layer and a thirteenth film layer in sequence from bottom to top to obtain coated glass; S4, sintering treatment: sintering the coated glass at 650°C for 400s; S5. Lamination treatment: 0.76 mm transparent PVB is used as a glue layer to perform lamination treatment between the thirteenth film layer on the outer glass substrate and the second surface of the inner glass substrate to obtain a high-transmittance double-silver-coated laminated glass.

7. The method for preparing high-transmittance double-silver coated laminated glass for automobile windshield according to claim 6, characterized in that: Before the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥61%, and the visible light reflectivity of the glass surface of the coated glass is ≤8%; After the sintering treatment in step S4, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤9%.

8. The method for preparing high-transmittance double-silver coated laminated glass for automobile windshield according to claim 7, characterized in that: After the lamination treatment in step S5, the visible light transmittance of the glass surface of the coated glass is ≥73%, and the visible light reflectivity of the glass surface of the coated glass is ≤11%.

9. The method for preparing high-transmittance double-silver coated laminated glass for automobile windshield according to claim 8, characterized in that: After the lamination treatment in step S5, the coating surface of the coated glass reflects light at an incident angle of 8° with an A value of -8.96±2.5 and a B value of -11.79±2.5; After the lamination treatment in step S5, the reflected light A value of the coated surface of the coated glass at an incident angle of 60° is -1.89±2.5, and the reflected light B value is -5.06±2.5; After the lamination treatment in step S5, the glass surface of the coated glass reflects light at an incident angle of 8° with an A value of -6.77±2.5 and a B value of -13.46±2.5; After the lamination treatment in step S5, the glass surface of the coated glass reflects light at an incident angle of 60° with an A value of -8.96±2.5 and a B value of -11.79±2.

5.

10. The method for preparing high-transmittance double-silver coated laminated glass for automobile windshield according to claim 9, characterized in that: The light transmittance of the high-transmittance double-silver coated laminated glass is more than 70%, the glass haze is 0.36%, the shading coefficient is 44.1%, and the total solar energy transmittance is 38.1%.